2018
DOI: 10.31632/ijalsr.2018v01i02.004
|View full text |Cite
|
Sign up to set email alerts
|

Hafnia Alvei Bacteremia Following Bronchopneumonia in an Eleven Month Old Child: A Case Report From a Tertiary Care Hospital in Nepal

Abstract: Hafnia alvei one of the members of family Enterobacteriaceae are related to infections that are uncommon. Believed to be an opportunistic pathogen, it is responsible for causing invasive infections in debilitated elderly people with underlying illnesses. Hafnia alvei infections, however, are extremely rare among immunocompetent neonates. We hereby, report a case of Hafnia alvei bacteremia following bronchopneumonia in an eleven month old male child who was apparently healthy and immunocompetent. To the best of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Hafnia alvei belongs to the Enterobacteriaceae family and is related to uncommon infections. It is considered an opportunistic pathogen that causes invasive infections in debilitated elderly with underlying diseases (Baral et al, 2018). Baral et al (2018) reported a case of bacteremia caused by Hafnia alvei resulting in bronchopneumonia in an 11-month-old child.…”
Section: Identification Of Psychotropic Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hafnia alvei belongs to the Enterobacteriaceae family and is related to uncommon infections. It is considered an opportunistic pathogen that causes invasive infections in debilitated elderly with underlying diseases (Baral et al, 2018). Baral et al (2018) reported a case of bacteremia caused by Hafnia alvei resulting in bronchopneumonia in an 11-month-old child.…”
Section: Identification Of Psychotropic Bacteriamentioning
confidence: 99%
“…It is considered an opportunistic pathogen that causes invasive infections in debilitated elderly with underlying diseases (Baral et al, 2018). Baral et al (2018) reported a case of bacteremia caused by Hafnia alvei resulting in bronchopneumonia in an 11-month-old child. Díaz et al (2017) presented a clinical case of a 40-year-old patient with no pathological history affected by a prolonged febrile state.…”
Section: Identification Of Psychotropic Bacteriamentioning
confidence: 99%
“…This bacterium is widely distributed in water, soil and food and is also part of the normal intestinal microbiota of mammals, marsupials, birds, reptiles, fish, invertebrates and insects (15,30,31). In humans, it is described as an unusual opportunistic pathogen causing nosocomial (18) or community infections (32,33). This bacterium is not a common pathogen in animals (15), although it has been isolated in some cases (18)(19)(20)34), but never has been isolated from a pyometra.…”
Section: Discussionmentioning
confidence: 99%
“…Their etiology varies with age and geography. Infrequent bowel movements and difficulty doi:10.31674/mjn.2023.v15i02.012 passing stool, along with neurological issues and common waterborne infections like diarrhoea, polio, and meningitis, are associated with the waterborne pathogen H. alvei, with the gastrointestinal tract being the main portal of entry for bacteremia and subsequent meningitis (Nayak et al, 2018;Hossain, Ali, & Islam, 2021). The fatality rate depends on age and the bacterium in question, typically ranging from 3% to 19% in developed countries (Ministry of Health, Morocco, 2010).…”
Section: Introductionmentioning
confidence: 99%